Proceedings of the First African Conference on Human Computer Interaction 2016
DOI: 10.1145/2998581.2998582
|View full text |Cite
|
Sign up to set email alerts
|

Sociality, Tempo & Flow

Abstract: Ridesharing has become a hot topic in research and in the media, largely because of the recent rise of platforms like Lyft and Uber. Yet shared taxis and paratransit services have played central roles in many African countries' transport systems for years. We conducted an ethnographic study of shared taxis in Windhoek, Namibia, to understand how ridesharing is achieved in this setting, including the drivers' orientations, concerns and practices, and their consequences for their passengers. Our findings lead us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Like others [23], we believe that workplace technology should enable agency, that is it should enhance the users' capacity to act [51], rather than controlling and constraining practice. A number of Prayana's features reflect our concern to support driver and collector agency.…”
Section: Designing For Agencymentioning
confidence: 71%
“…Like others [23], we believe that workplace technology should enable agency, that is it should enhance the users' capacity to act [51], rather than controlling and constraining practice. A number of Prayana's features reflect our concern to support driver and collector agency.…”
Section: Designing For Agencymentioning
confidence: 71%
“…These forms of ‘frictions’ constitute what Cresswell (2014: 112) calls the ‘grip of worldly encounters’. Along these lines, researchers have begun to highlight the frictions generated when the assumed universality of platform‐mediated logics, technology, and flows of capital interact with local social infrastructures (Peters, 2020; von Vacano, 2021), topography, tempo, and pace (Kasera et al ., 2016; Qadri, 2021), and incumbent actors on the streets of Asian cities (Kumar et al ., 2018; Jack, 2020). These three approaches to friction, analysing its visible, political, and spatially divergent characteristics, make it highly relevant for understanding the dynamics of mobilities and livelihoods of motorbike taxi driver groups in Hanoi.…”
Section: Conceptualising Mobility Frictions Platform Economies and Ur...mentioning
confidence: 99%
“…Ride-hailing has been less extensively studied from a workers' perspective in the Global South (Ahmed et al, 2016;Kasera, O'Neill, and Bidwell, 2016;Kumar, JafarNaimi, and Morshed 2018;Prabhat, Nanavati, and Rangaswamy 2019;Fleitoukh and Toyama, 2020). In one of the earliest studies, Kasera, O'Neill, and Bidwell (2016) noted that the design of P2P platforms like Uber did not fit into the work practices and temporal rhythms of drivers operating shared taxis in Namibia and was therefore not viable for them. In India, Ahmed et al (2016) showed how drivers using Ola had little information on or understanding of central features of their work such as ride allocation, pricing, and evaluation.…”
Section: Working For Ride-hailing Platformsmentioning
confidence: 99%